Morphological studies and management of Beetal goats in its native tract - ALAM, SAFEER; SINGH, P K; KHAN, B U (The Indian Journal of Animal Sciences, 2011)
A study was conducted through systematic survey of 25 villages of the four districts of Punjab, viz. Gurdaspur, Amritsar, Ferozpur and Ludhiana, for phenotypic characterization of Beetal goats. During the survey 1726 goats of different ages and sexes were studied for physical traits and 66 flocks were studied to know the m.anagement practices followed by the goat farmers. The physical traits, viz. colour of coat, retina, hooves and hom, orientation of hom and ear, structure of head, tail pattern and shape of udder and teats were recorded for the animals of both the sexes belonging to 3 age groups. The physical characters of the breed included predominately black or brown coat colour with white spots of different sizes, roman nose but not as prominent as in Jamunapari breed. Nine different body measurements were also recorded on the animal belonging to different age groups and sexes. The management practices were studied on different aspects of housing, breeding, feeding. Since the goat owners belong to poor farnler community and there is shrinkage in grazing land in the breeding tract of Beetal goats, the breed is declining in~number very fast. Hence immediate steps should be taken up to save this breed in its natural habitat.Â